2004
DOI: 10.1063/1.1652654
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermocapillary effect and interfacial heat release on convective oscillations in a two-layer system

Abstract: The oscillatory convection for a real system of fluids under the joint action of buoyancy and thermocapillary effect or in the presence of the interfacial heat release is investigated. The nonlinear development of the oscillatory instability is studied. In the case of periodic boundary conditions, regimes of traveling waves and pulsating traveling waves are predicted. For different types of boundary conditions, the period doubling bifurcation is obtained. It is shown that the region of the Grashof number value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…The presence of a constant, spatially uniform heat release at the interface can lead to the appearance of an oscillatory instability (Nepomnyashchy and Simanovskii 2004). The simulations in Nepomnyashchy and Simanovskii (2004) have been performed for a single value of the modified Grashof number, corresponding to an interfacial heat sink.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a constant, spatially uniform heat release at the interface can lead to the appearance of an oscillatory instability (Nepomnyashchy and Simanovskii 2004). The simulations in Nepomnyashchy and Simanovskii (2004) have been performed for a single value of the modified Grashof number, corresponding to an interfacial heat sink.…”
mentioning
confidence: 99%
“…The simulations in Nepomnyashchy and Simanovskii (2004) have been performed for a single value of the modified Grashof number, corresponding to an interfacial heat sink. In the recent paper (Simanovskii 2013a), the influence of an interfacial heat release and heat consumption on convective oscillations has been studied in the case of rigid heat-insulated lateral walls, corresponding to a closed cavity.…”
mentioning
confidence: 99%
“…Recently, many studies [14][15][16][17][18] focused on the two combinations of two-layer fluid system: Silicone oil (10cSt) over Fluorinert (FC70) and Silicone oil (2cSt) over water, since Degen et al [17] have conducted the experimental investigations on these two different pairs of fluids. In Degen's experimental studies, for the two-layer system of Silicone oil (10cSt) over Fluorinert (FC70), the oscillation convection observed at the onset are in good agreement with the linear stability analysis results when considering or not considering the Marangoni effect [14,15,18] . However, the oscillatory instability behavior in the two-layer system of Silicone oil (2cSt) over water could not be predicted by the previous linear stability analysis.…”
Section: Indroductionmentioning
confidence: 99%
“…~1mm on earth) or in microgravty environment, the Marangoni effect plays an important role on the convective instability. Both linear stability analysis [13][14][15] and numerical simulation study [16] have shown that the oscillatory region is enlarged through the coupling of Rayleigh instability and Marangoni effect.…”
Section: Indroductionmentioning
confidence: 99%
“…More physical mechanisms of the instabilities in a two-layer system can be referred in many previous works. [1][2][3][4][5][6][7][8] In the absence of vibration and Marangoni effect, there are two different cases where oscillatory instabilities have been predicted. The first case is that the densities of fluids are close to each other so that the deviations of the densities with respect to temperature are comparable with the density difference of the reference state, and the oscillation may be self-sustained as interfacial waves.…”
Section: Introductionmentioning
confidence: 99%